2022
DOI: 10.1051/cagri/2022019
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining community-managed rural water supply systems in severe water-scarce areas in Brazil and Tunisia

Abstract: In many countries, the challenge of sustaining rural water supplies is entrusted to community organizations, which have difficulties in performing durably the operation, maintenance and cost recovery of rural water supply systems. This paper analyzes how rural communities struggle to ensure a sustainable access to water, while seeking close interaction with outside actors such as the State, NGOs, and politicians. The analysis is based on field observations, interviews and participatory workshops in four commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Special attention was paid to water resources, due to their importance in the agricultural and domestic activities in the context of frequent droughts in the region. The access to water for multiple uses is shaping the territory and the relation between the communities' members in the Forquilha watershed (Gasmi et al, 2022). We triangulated the collected data with secondary data from the Institute for Research and Economic Strategy of Ceará (IPECE), the Brazilian Institute of Geography and Statistics (IBGE), through the 2017 Agricultural Census, and the Observatory of Family Farming of Ceará.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Special attention was paid to water resources, due to their importance in the agricultural and domestic activities in the context of frequent droughts in the region. The access to water for multiple uses is shaping the territory and the relation between the communities' members in the Forquilha watershed (Gasmi et al, 2022). We triangulated the collected data with secondary data from the Institute for Research and Economic Strategy of Ceará (IPECE), the Brazilian Institute of Geography and Statistics (IBGE), through the 2017 Agricultural Census, and the Observatory of Family Farming of Ceará.…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, various infrastructures for capturing and storing domestic water were put in place in remote areas of the Ceará state, but water security is still not guaranteed for all rural families. As showed by recent research in the same area (Gasmi et al, 2022), a family unit may manage several water sources and infrastructures in order to deal with water scarcity (i.e., shallow well, deep well, dam, cistern, piped water, and tank trucks). Thus, families develop strategies for maintaining their multiple uses, especially during the dry season, by alternating and/or mixing water sources, as explained by a female farmer:…”
Section: Gendered Visions Of the Future And Migration Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of rural Nepal, a study showed that using methodologies for drinking water supply projects that involve community members in collaborative planning, implementation, and maintenance allows for location-appropriate systems that are more sustainable and effective than generalized systems. [5] Various research articles and papers have been published regarding the factors for the determination of the sustainability of rural water supply projects. The main sustainability factors generally adopted are economic, technical, institutional, social and environmental factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In least-developed countries like Bangladesh, these systems often fail at the community level due to improper operation and maintenance [ 76 , 77 ], as well as uninformed site selection that does not consider the needs of the beneficiaries. Organizational and financial aspects play a crucial role in the sustainability of community-based water supply projects in these countries [ 78 ]. Furthermore, weak governance and regulation often hinder the establishment of effective institutional structures and tariff modalities [ 79 ].…”
Section: Introductionmentioning
confidence: 99%